Legal basis for tourism development in Kazakhstan - Abdukarimova, Z.T.; Surkova, S.S. (Bulletin of the Karaganda University “Law Series”, 2018)
The relevance of research of questions of impact of the accepted norms in Kazakhstan for development of tourism lies in the fact that the prerequisites for the development of tourism has changed in recent years. A market was emerged administrative structures was emerged, but the problem with the development of tourism remains a big problem. In June, 2017 in Kazakhstan was accepted the Concept of development of tourist branch till 2023. One of the reasons hampering the accelerated development of tourism, mentioned in the Concept, is the insufficient level of regulatory regulation of the tourism industry. The main purpose of the project was the need to research the improvement of legislation in the field of tourism for the attractiveness of our country, improve its competitiveness, and develop directions for improving the tourist structure, not only for tourists but also for investors. The result of the work will be proposals for improving legislation in this area, informing government agencies about the norms that do not allow tourism development in Kazakhstan, and developing proposals on ensuring the safety of tourists, procedures directly or indirectly regulating the development of tourism as a business area.